Dual Inhibition of Parasitic Targets: A Valuable Strategy to Treat Malaria and Neglected Tropical Diseases - Previti, Santo; Di Chio, Carla; Ettari, Roberta; Zappalà, Maria (Current Medicinal Chemistry, 2022)
Despite the countless efforts made in the last decades, malaria and neglected tropical diseases remain a high-impact health problem in developing countries. Malaria is one of the most severe parasitic diseases, with over 200 million cases and 400,000 deaths in 2019. Parasitic diseases caused by trypanosomatidae, namely Human African Trypanosomiasis, Chagas disease, and leishmaniasis, register the highest rates of mortality amongst all the neglected tropical diseases. In this scenario, chemotherapy remains the first strategy, which aims to control and eliminate these diseases. However, the use of outdated, unsafe, and poorly effective drugs, together with the onset of resistance, prompted the researchers to identify new and valid targets. The innovative idea, aimed at the development of multi-target ligands addressing two different targets playing key roles in parasite survival, could represent a valuable strategy. Thanks to this approach, the wellknown limitations characterizing the antiparasitic drugs, such as toxicity, rapid resistance onset and narrow spectrum of action, could be overcome. In this review, we now describe the most recent multi-target ligands endowed with antiparasitic effects reported in the literature, focusing our attention on their binding with the targets, inhibitory activities, and potential therapeutic applications.
Keywords: malaria